Treatment Outcome of a Combined Dose-Escalated Treatment Regime With Helical TomoTherapy® and Active Raster-Scanning Carbon Ion Boost for Adenocarcinomas of the Head and Neck - Akbaba, Sati; Mock, Andreas; Hoerner-Rieber, Juliane; Held, Thomas; Katayama, Sonja; Forster, Tobias; Freudlsperger, Christian; Rieken, Stefan; Herfarth, Klaus; Plinkert, Peter; Debus, Juergen; Adeberg, Sebastian (Frontiers in Oncology, 2019)
Introduction Data regarding treatment and survival outcome of patients with adenocarcinoma of the head and neck are limited to case reports and case series. As a consequence of lacking evidence, treatment guidelines do not exist. We aimed to analyze the effect of a bimodal irradiation regime with intensity modulated radiotherapy (IMRT) and carbon ion boost on local control (LC) and survival in adenocarcinoma patients for a large patient collective. Materials and Methods Patient records of eighty consecutive patients treated between 2009 and 2018 were analyzed retrospectively and Kaplan-Meier estimates for LC, overall survival (OS) and progression-free survival (PFS) were compared among patients with salivary gland adenocarcinoma (SGAC), salivary duct adenocarcinoma (SDAC) and intestinal-type adenocarcinoma (ITAC) according to the World Health Organization. Prognostic factors were identified using the log-rank test and cox-regression modelling. Toxicity was assessed according to the Common Terminology Criteria for Adverse Events. Results Median follow-up was 41 months. The 3-year and estimated 5-year Kaplan-Meier rates for all patients were 83% and 75% for LC, 74% and 50% for OS and 60% and 53% for PFS, respectively. While bimodal RT for ITAC resulted in a significantly decreased 3-year LC rate of 50% vs. 93% for each SGAC and SDAC (p<0.01), no statistical significant survival differences could be identified across the three groups regarding OS (p=0.08) and PFS (p=0.063). 3-year OS was 88% for SGAC, 78% for SDAC and 67% for ITAC and 3-year PFS was 72% for SGAC, 53% for SDAC and 44% for ITAC, respectively. Nevertheless, in subgroup analysis, OS for ITAC was significantly worse compared to SGAC (p=0.024). In multivariate analysis, bilateral tumor side (vs. unilateral) solely could be identified as independent negative prognostic factor for LC (p<0.01). Treatment was well tolerated with 21% acute (n=17) and 25% (n=20) late grade ≥3 toxicities. Conclusion Radiotherapy including active raster-scanning carbon ion boost for relatively radio resistant adenocarcinomas of the head and neck resulted in favorable survival outcome for salivary gland and salivary duct adenocarcinomas with moderate toxicity. However, local control and prognosis for bilateral intestinal-type adenocarcinomas seem to remain low even after dose-escalation.